Knowledge, attitudes, and practices related to augmented renal clearance among pediatricians in China: A cross-sectional study. Issue 32 (13th August 2021) - Zhou, Ran; Fang, Yuting; Wang, Chunyan; Zhou, Shusheng
Abstract : Abstract: Our purpose was to assess pediatricians' knowledge of augmented renal clearance (ARC). We conducted cross-sectional analyses of 500 pediatricians from 16 tertiary hospitals in Anhui Province, China. Pediatricians provided demographic information and were asked questions about their knowledge of ARC, including risk factors, evaluation tools, and the impact on patient prognosis, with a focus on the attitude and practice of pediatricians related to adjusting vancomycin regimens when ARC occurs. A total of 491 valid questionnaires were finally included, only 276 pediatricians stated that they "know about ARC." Compared with the "do not know about ARC" group, the "know about ARC" group was younger (43.7 ± 8.0 vs 48.0 ± 7.9, P  < .001), and their main source of ARC knowledge was from social networking platforms. A total of 193 (70%) chose at least 4 of the following factors as risk factors for children with ARC: severe trauma, sepsis, burns, major surgery, lower disease severity, and hematological malignancies. A total of 110 (40%) and 105 (38%) pediatricians chose the Schwartz formula and cystatin C, respectively, as the indicators to evaluate the renal function of ARC children. Concerning the estimated glomerular filtration rate threshold to identify ARC children, 201 (73%) pediatricians chose 130 mL/min/1.73 m 2, while 55 (20%) chose "age-dependent ARC thresholds." Overall, 220 (80%) respondents indicated that ARC would impact the treatment effect of vancomycin, but 149/220 (68%) were willing to adjust the vancomycin regimen; only 22/149 (8%) considered that the dose should be increased, but no one knew how to increase. Regarding the prognosis of ARC children, all respondents chose "unclear." ARC is relatively common in critically ill children, but pediatricians do not know much about it, as most of the current knowledge is based on adult studies. Furthermore, ARC is often confused with acute kidney injury, which would lead to very serious treatment errors. Therefore, more pediatric studies about ARC are needed, and ARC should be written into official pediatric guidelines as soon as possible to provide reference for pediatricians.